EFEKTIVITAS METODE TBL (TEAM BASED LEARNING) PADA PROSES PEMBELAJARAN DI MASA PANDEMI COVID-19 - Kamaludin, Fahmi; Rosadi, Andrea Salsabila; Herkan, Muhamad Thariq; Makkiyah, Feda Anisah (Journal of Religion and Public Health, 2021)
The COVID-19 pandemic has prompted a shift in learning method, from synchronous face-to-face to synchronous online. Traditional online learning methods, on the other hand, have proven ineffective. As a result, a new method is required to make learning more motivating and to achieve the desired learning outcome. Team-based learning is one of the newer learning methods that is gaining popularity today (TBL). TBL is a learning method that emphasizes team collaboration with minimal human resources unlike problem based learning. Students are expected to be more active in learning activities and to collaborate within their groups. However, some question whether online TBL is as effective as offline TBL. The purpose of this paper is to learn about the advantages and disadvantages of online TBL.  This literature review searched for English-language journals in the last 5 years (PubMed and NCBI databases) which focused on TBL online and offline learning. The satisfaction of students in the survey showed good results (85%). However, there was a weakness of online TBL such as decreased verbal communication, collaboration and leadership of students.  In contrast, student’s learning experiences and student’s written communication skills showed no difference with offline learning. Online TBL still proves effective with providing more space for student’s communication.keywords: Team Based Learning, Literatur Review, Pandemic Event Abstrak Pandemi COVID-19 telah mendorong perubahan metode pembelajaran, dari secara tatap muka menjadi secara daring. Namun, metode pembelajaran daring konvensional terbukti tidak efektif. Oleh karena itu, dibutuhkan sebuah metode baru agar pembelajaran menjadi lebih memotivasi dan tujuan pembelajaran akan tercapai. Salah satu metode pembelajaran baru yang sedang populer saat ini adalah team based learning (TBL). TBL adalah metode pembelajaran yang menekankan kolaborasi antar tim. Pada metode ini, siswa dituntut untuk lebih aktif dan harus bekerja sama dengan kelompok mereka. Namun, terdapat beberapa keraguan apakah TBL yang dilakukan secara daring sama efektifnya dengan TBL yang dilakukan secara luring. Tulisan ini bertujuan untuk mencari kelebihan dan kekurangan metode TBL daring. Literature review ini mencari dari jurnal berbahasa inggris 5 tahun terakhir (database PubMed dan NCBI) yang berfokus pada TBL daring dan luring. Hasilnya, kepuasan siswa pada survei mendapatkan hasil yang baik (85%). Namun, terdapat kekurangan dari TBL daring seperti menurunnya komunikasi verbal dan kepemimpinan pada siswa. Sebaliknya, pengalaman belajar dan kemampuan komunikasi tertulis siswa menunjukan tidak ada perbedaan dengan pembelajaran luring. Kesimpulannya, TBL daring terbukti efektif dengan memberikan lebih banyak ruang untuk siswa berkomunikasi.Kata kunci : Team Based Learning, literatur review, peristiwa pandemi